2016
DOI: 10.4172/2155-6156.1000693
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Hypomagnesaemia and Glycemic Control in Children with Type 1 Diabetes Mellitus

Abstract: Background: Hypomagnesaemia is common in adult patients with both Type 1 Diabetes Mellitus (T1DM) and Type 2 Diabetes MellitusT2DM, especially in poorlycontrolled and chronically treated adults. However, to our knowledge, little research has addressed the relationship between serum magnesium levels and diabetes in children. The aim of the present study was to evaluate magnesium levels and examine their possible association with glycemic control in children with T1DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…is result is similar with the study of many researchers. 6,9,15,16 Inconsistent with our result, some researchers did not observe any relationship between serum magnesium and glycemic status [17][18][19] . is di erence could be attributed to the di erence in study populations, degree of diabetic control among them and to the di erent methods of evaluating serum magnesium and HbA 1c .…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…is result is similar with the study of many researchers. 6,9,15,16 Inconsistent with our result, some researchers did not observe any relationship between serum magnesium and glycemic status [17][18][19] . is di erence could be attributed to the di erence in study populations, degree of diabetic control among them and to the di erent methods of evaluating serum magnesium and HbA 1c .…”
Section: Discussionsupporting
confidence: 55%
“…A recent study in Egypt showed that there were 37.3% of the diabetic subjects had hypomagnesaemia. 9 Seyoum et al 13 found a higher percentage of hypomagnesaemia (65%) in their study. Contrary to our result, Zargar et al 14 , did not found any signi cant alteration in plasma magnesium level in type 1 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…On the other hand study done in Egypt on 25 type I DM patients had shown significantly low serum magnesium levels in cases as compared to controls, also they have found negative correlation between duration of illness and serum magnesium levels. A study done in Egypt observed that the relation between serum magnesium levels and glycemic control, on 150 type I DM patients, it was observed that 37.3% of patients had hypomagnesemia and those patients had higher HbA1C levels as compared to rest [15].…”
Section: Discussionmentioning
confidence: 97%
“…The results of the study show that serum magnesium levels were lowered in children and adolescents with T1DM. Also they have found low serum magnesium levels association with an increased risk of poor glycemic control, potentially contributing to the early development of diabetic complications [1].…”
Section: Introductionmentioning
confidence: 99%